Simple and General Procedure for the Synthesis of α,β-Alkynyl Ketones from Nitriles Using Alkynyldimethylaluminum Reagents - Korbad, Balaji L.; Lee, Sang-Hyeup (Synlett, 2013)
A simple and efficient approach for the synthesis of α,β-alkynyl ketones from nitriles and alkynyldimethylaluminum reagents, derived from trimethylaluminum and alkynes, is described. This methodology provides access to a wide range of α,β-alkynyl ketones with aliphatic, aromatic, and heteroaromatic substituents in moderate to high yield (53–90%). In the cases of aryl-substituted nitriles, the product can also be obtained as α,β-alkynyl N-H ketimines in high yield (88–93%).
Keywords: α,β-alkynyl ketones; α,β-alkynyl N-H ketimines; alkynes; trimethylaluminum; nitriles